Transport disadvantage and car dependency in Rural Ireland - CAULFIELD, BRIAN; Benevenuto, Rodolfo; Carroll, Páraic (My University, 2017)
This paper explores the concepts of car dependency and deprivation and the correlation between them in areas of rural Ireland as a means of highlighting incidences of possible forced car ownership with the use of GIS. Challenges related to the prevalence ofthe private car as the main or in some cases the only form of mobility for people living in rural Ireland areexamined. Three out of four journeys outside of Dublin were made by car in 2016 [1], and car dependency tends to be even more exacerbated when there is a need to travel over longer distances within rural areas [2]. However, potential ways of promoting sustainable ‘car-shedding’ behaviour [3] in these areas must equally consider the pressing issue of transport disadvantage. The increasing car ownership within this context may not be necessarily caused by economic growth. Rather, it can be a sign of deprivation and necessity leading to forced car ownership (FCO). Hence, this paper will examine the existing gap between the transport necessity and the provision of reliable public transport in rural Ireland, which is frequently attributed as a major determinant of FCO. This study presents the following: (i) a delineation of the complexity of FCO and the barriers to achieving a favourable solution in suchareas experiencing poor public transport accessibility; (ii) an analysis of the correlation between transport disadvantage and deprivation in rural Ireland by means of a deprivation index administered through geospatial and statistical tools, and; (iii) an evaluation of the performance of measures currently in place to tackle such issues (e.g. local services and community transport schemes). GIS tools and statistical indicators are applied to identify the most affected areas related to car-dependency and transport disadvantage and a further discussion focuses on these hot-spots to suggest potential transport improvements which could provide a holistic solution to this topic of national importance.
ITRN
Keywords: Transport; Car dependency; Car ownership; Public transport accessibility; Smart & Sustainable Planet; Transport